FRI0484 IGG4 Related Hypertrophic Pachymeningitis: Diagnostic Approach and Therapeutic Outcomes. (15th July 2016) - Bozzalla Cassione, E.; Lanzillotta, M.; Passerini, G.; Tresoldi, M.; Sabbadini, M.G.; Della Torre, E.
Abstract : Background: IgG4 Related Disease (IgG4-RD) is a fibro-inflammatory condition characterized by IgG4 positive lymphoplasmacytic infiltrate of affected tissues. Meningeal involvement, typically of the dura mater, represents one of the most challenging manifestations of IgG4-RD in terms of diagnostic and therapeutic approach (1). Case reports have suggested the potential utility of cerebrospinal fluid (CSF) IgG4 measurement in the differential diagnosis of IgG4 Related Hypertrophic Pachymeningitis (IgG4-RHP) (2). Objectives: To assess the usefulness of CSF analysis in the diagnosis of IgG4-RHP. To describe the clinical, serological and radiological response of IgG4-RHP to different therapeutic regimens. Methods: Five pts (3 females and 2 male) with biopsy-proven IgG4-RHP were evaluated through serological, radiological, and microbiological studies before and after immunosuppressive treatment. CSF analysis for intrathecal IgG4 production was performed in all pts before therapy, and in 3 pts after therapy. Serum and CSF IgG subclasses were measured through ELISA assays. Intrathecal IgG subclasses production was assessed through the IgG Index and the IgG-LOC. Results: Cranial nerve deficit was the common clinical presentation of HP. Magnetic resonance imaging showed thickening of the dura mater in all pts. Serological and CSF results are reported in Table 1 . CSF analysis before treatment revealed increased IgG4 values, IgG4 Index, and IgG4-LOC in all pts with an average value of 9.64 mg/dL (normal 0.01–0.33 mg/dL), 4.14 (normal <0.7) and 8.15 (normal <0) respectively. Pt 1 was treated with intravenous (i.v.) methylprednisolone, oral prednisone, i.v. cyclophosphamide, and, rituximab; Pt 2 was treated with oral prednisone and methotrexate; Pt 3 was treated with oral prednisone; Pt 4 was treated with oral prednisone, methotrexate, azathioprine, and oral cyclophosphamide; Pt 5 was treated with i.v. methylprednisolone, cyclophosphamide, and rituximab. Patient 2, 3 and 4 responded to therapy with a marked clinical improvement and an almost complete resolution of the meningeal thickening. Pt 1 had a minimal response to therapy with only a partial reduction of the meningeal thickening. Patient 5 had a poor response to therapy with no improvement of the meningeal thickening. CSF IgG4 (0.07 mg/dL), IgG4 Index (0.23) and IgG4-LOC (0) normalized after treatment in Patient 4, and decreased without normalization in Pts 1 and 5 (CSF IgG4 0.54 and 3.99 mg/dL, IgG4 Index 0.81 and 5.1, and IgG4-LOC 0.09 and 3.46, respectively). Conclusions: CSF analysis of intrathecal IgG4 production represents a useful tool for orienting the differential diagnosis of idiopathic HP especially when meningeal biopsy is not feasible. The variability in the responses to immunosuppressive therapies might be due to differences in the disease phenotypes and drug penetration in meningeal layers. References: Della-Torre E, Lu LX, Stone JH, et al. IgG4-Related Hypertrophic Pachymeningitis: Clinical Features, Diagnostic Criteria, and Treatment. JAMA Neurol. 2014 Apr 14. Della-Torre E, Galli L, Franciotta D, et al. Diagnostic value of IgG4 Indices in IgG4-Related Hypertrophic Pachymeningitis. J. Neuroimmunol. 2013 Oct 22. Disclosure of Interest: None declared